2021
DOI: 10.1109/tvcg.2020.2999197
|View full text |Cite
|
Sign up to set email alerts
|

Virtual Co-Embodiment: Evaluation of the Sense of Agency While Sharing the Control of a Virtual Body Among Two Individuals

Abstract: In this paper, we introduce a concept called "virtual co-embodiment", which enables a user to share their virtual avatar with another entity (e.g., another user, robot, or autonomous agent). We describe a proof-of-concept in which two users can be immersed from a first-person perspective in a virtual environment and can have complementary levels of control (total, partial, or none) over a shared avatar. In addition, we conducted an experiment to investigate the influence of users' level of control over the sha… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
37
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 50 publications
(38 citation statements)
references
References 77 publications
1
37
0
Order By: Relevance
“…Twenty volunteers participated in the experiment (all male, mean 21.35 years old ± 1.5 standard deviation (SD)). The sample size was based on previous embodiment (Fribourg et al, 2020) and motor control (Ganesh, et al, 2014) studies involving interaction between human dyads. This number corresponds to an effect size of 0.7, alpha = 0.05, power = 0.8 using the G*Power 3.1 (Faul, Erdfelder, Lang, & Buchner, 2007;Faul, Erdfelder, Buchner, & Lang, 2009).…”
Section: Transparent Methods Participantsmentioning
confidence: 99%
See 1 more Smart Citation
“…Twenty volunteers participated in the experiment (all male, mean 21.35 years old ± 1.5 standard deviation (SD)). The sample size was based on previous embodiment (Fribourg et al, 2020) and motor control (Ganesh, et al, 2014) studies involving interaction between human dyads. This number corresponds to an effect size of 0.7, alpha = 0.05, power = 0.8 using the G*Power 3.1 (Faul, Erdfelder, Lang, & Buchner, 2007;Faul, Erdfelder, Buchner, & Lang, 2009).…”
Section: Transparent Methods Participantsmentioning
confidence: 99%
“…Sharing thus enables multiple individuals to collaborate and contribute in the task performed by an avatar potentially decreasing the workload for each user and improving task performance. Sharing of body parts has been shown to lead to changes in the perceived ownership and agency (Fribourg et al, 2020;Hagiwara et al, 2019). On the other hand, it still remains unclear whether and how shared embodiment affects an individual's motor behavior.…”
Section: Introductionmentioning
confidence: 99%
“…In this study, we explore a new concept called “virtual co-embodiment” where two or more users embody one avatar to collaboratively perform joint tasks. Co-embodiment can be achieved in several ways such as reflecting average movements (or movements in different ratios of control) of multiple users to one avatar/robot 7 , 8 , allowing multiple users to control different sections of one avatar limb/robotic arm 9 , and allowing each user to fully control separate limbs of one avatar 10 , 11 . We are focusing on this third method; We utilized an avatar of which left and right limbs could be controlled by two different individuals at the same time while both of them were immersed in the first-person view of the virtual avatar.…”
Section: Introductionmentioning
confidence: 99%
“…1 A) in VR and showed that the movements of the shared avatar were straighter, and less jerky compared to the movements of the individual participants and the solo body avatar. Fribourg et al 7 introduced the concept of “virtual co-embodiment” and showed that the participants were good at estimating their real levels of control but significantly overestimated their “sense of agency” when they could anticipate the motion of the avatar. These previous studies on virtual co-embodiment have studied avatars of which the movements were determined by averaging the movements of the two participants in real time (occasionally in different ratios of control).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation